2011
DOI: 10.1162/jocn_a_00084
|View full text |Cite
|
Sign up to set email alerts
|

Does Semantic Context Benefit Speech Understanding through “Top–Down” Processes? Evidence from Time-resolved Sparse fMRI

Abstract: Abstract■ When speech is degraded, word report is higher for semantically coherent sentences (e.g., her new skirt was made of denim) than for anomalous sentences (e.g., her good slope was done in carrot). Such increased intelligibility is often described as resulting from "top-down" processes, reflecting an assumption that higher-level (semantic) neural processes support lower-level (perceptual) mechanisms. We used time-resolved sparse fMRI to test for top-down neural mechanisms, measuring activity while parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
160
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 76 publications
21
160
0
Order By: Relevance
“…Error bars indicate SEM, corrected for within-subject comparisons (Loftus and Masson, 1994). Davis et al, 2011;Giraud et al, 2004;Narain et al, 2003;Obleser et al, 2007a;Okada et al, 2010;Scott et al, 2000Scott et al, , 2006. Consistent with these studies, our results show that activation in a fronto-temporal network including the left IFG and the medially adjacent anterior insula, as well as left posterior STS/MTG is modulated by speech intelligibility.…”
Section: Regions Negatively Correlated With Snr (Or Positively With Nsupporting
confidence: 89%
See 3 more Smart Citations
“…Error bars indicate SEM, corrected for within-subject comparisons (Loftus and Masson, 1994). Davis et al, 2011;Giraud et al, 2004;Narain et al, 2003;Obleser et al, 2007a;Okada et al, 2010;Scott et al, 2000Scott et al, , 2006. Consistent with these studies, our results show that activation in a fronto-temporal network including the left IFG and the medially adjacent anterior insula, as well as left posterior STS/MTG is modulated by speech intelligibility.…”
Section: Regions Negatively Correlated With Snr (Or Positively With Nsupporting
confidence: 89%
“…A subset of the studies on speech intelligibility have also found the left anterior hippocampus to be sensitive to speech intelligibility, and this finding has been related to the role of this brain region in verbal memory and in processing meaning in verbal stimuli (Davis and Johnsrude, 2003;Davis et al, 2011). Together, this literature suggests that left frontal regions work in concert with left anterior to posterior temporal regions involved in higher-level binding of meaning in connected speech to assist the effortful comprehension of degraded speech (Davis and Johnsrude, 2003;Davis et al, 2011;Obleser et al, 2007a;Okada et al, 2010).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…For experiments on speech comprehension, common experimental manipulations might be to compare speech stimuli that are comprehended or not comprehended due to auditory degradation, or that vary in the ease of comprehension due to the presence/ absence of lexical or semantic anomaly or ambiguity (e.g. Davis, Ford, Kherif, & Johnsrude, 2011;Rodd, Davis, & Johnsrude, 2005;Scott, Blank, Rosen, & Wise, 2000). It is also possible to contrast responses to a single set of stimuli while manipulating the behavioural response required (e.g.…”
Section: Overview Of Cognitive Neuroscience Methods For Studying Spokmentioning
confidence: 99%